Clubroot Symptoms and Resting Spore Production in a Doubled Haploid Population of Oilseed Rape (Brassica napus) Are Controlled by Four Main QTLs - Botero-Ramírez, Andrea; Laperche, Anne; Guichard, Solenn; Jubault, Mélanie; Gravot, Antoine; Strelkov, Stephen E.; Manzanares-Dauleux, Maria J. (Frontiers in Plant Science, 2020)
Clubroot, caused by Plasmodiophora brassicae Wor., is one of the most important diseases of oilseed rape (Brassica napus L.). The rapid erosion of monogenic resistance in clubroot-resistant varieties underscores the need to diversify resistance sources controlling disease severity and traits related to pathogen fitness, such as resting spore production. The genetic control of disease index (DI) and resting spores per plant (RSP) was evaluated in a doubled haploid population consisting of 114 winter oilseed rape lines, obtained from the cross ‘Aviso’ × ‘Montego’, inoculated with P. brassicae isolate ‘eH’. Linkage analysis allowed the identification of three quantitative trait loci (QTLs) controlling DI (PbBn_di_A02, PbBn_di_A04 and PbBn_di_C03). A significant decrease in DI was observed when combining effects of the three resistance alleles at these QTLs. Only one QTL, PbBn_rsp_C03, was found to control RSP, reducing resting spore production by 40%. PbBn_rsp_C03 partially overlapped with PbBn_di_C03 in a nucleotide-binding leucine-rich repeat (NLR) gene-containing region. Consideration of both DI and RSP in breeding for clubroot resistance is recommended for the long-term management of this disease.